The Prevalence of Cephalosporins resistance in Pseudomonas aeruginosa isolated from clinical specimens in Basra, Iraq - Zeina MM Alkhulaifi,; Khairallah AS Mohammed, (University of Thi-Qar Journal of Science, 2023)
Pseudomonas aeruginosa is gram negative rod bacterium.It is commonly found in soil, water, plants and humans. Notably, P. aeruginosa has become an emerging opportunistic pathogen in hospitals, which has a major threat to the global health systems, including Iraq. The purpose of this study is to determine the prevalence of cephalosporin resistance in Pseudomonas aeruginosa isolated from clinical samples. Pseudomonas aeruginosa strains were identified by standard microbiological procedures followed by PCR confirmation. Antibiotic susceptibility testing, for 5 antimicrobials, was conducted according to the Clinical and Laboratory Standard Institute (CLSI) standardized by disk diffusion methodsand VITEK 2 methods. Of the 160 clinical specimens, 81 were positive for P. aeruginosa.The results showed that 81 isolates were identified as Pseudomonasaeruginosa of which 97.53%,79%, 83%, 81.50 %, 100 and 80.30% were resistant to Cefoxitin, Ceftriaxone, Cefotaxime, Ceftazidime and Cefepime respectively. These findings highlighted a high prevalence rate of cephalosporins antibiotics resistance P. aeruginosa at Basra hospitals in Iraq.